Migration of radionuclides in arable land of Lithuania - Lubyte, Jadvyga; Antanaitis, Antanas (Journal of Environmental Engineering and Landscape Management, 2004)
The paper presents the investigation data on soil contamination by Cs and Sr during the period 1974–2000 in various climatic zones and geographical locations for various granulometric and mineralogic composition of the soil and also for different mineralogical rock composition. The data concerning the accumulation of these elements, their perpendicular distribution before and after the Chernobyl Atomic Power Plant (ChAPP) accident. Besides, the influence of long term fertilization by various NPK rates on the amounts of radionuclides in the soil is presented. It is determined that before the ChAPP accident an average activity of 137Cs and 90Sr was 6,8±1,8 Bq · kg−1 and 5,3±1,2 Bq · kg−1, respectively. The radioactivity of peat soils was 2–5 times larger than that of mineral soils. After the accident in the ChAPP the amount of 90Sr in control plots, in the layer of 0–20 cm has not changed. In some fields an average amount of 137Cs is 6,7–28,5 Bq · kg−1. Larger concentrations of radionuclides were detected in the southeastern, southern and western regions of Lithuania. The amount of 137Cs in the upper soil layer in the western region of Lithuania was 1,1–1,2 times larger than in the layer of 5–20 cm, and 1,3–2,5 times larger than in the layer of 20–40 cm. Distinction is not so noticeable in the middle and eastern regions of Lithuania, correspondingly 1,1–1,2 and 1,2–1,6 times. Migration of 90Sr and 137Cs from the soil to plants varies and depends on soil properties and types of plants. The coefficients of 137Cs and 90Sr movement from the soil to plants were 0,24–0,53 and 0,37–0,87, respectively. In most cases long term fertilization had no influence on 90Sr and 137Cs accumulation and migration in the soil. Radionuklidų migracija ariamuose Lietuvos dirvožemiuose Santrauka. Pateikti 1974–2000 m. atliktų skirtingų Lietuvos klimatinių ir gamtinių zonų įvairios dirvožemio granuliometrinės bei mineraloginės, taip pat uolienų mineralogines sudėties laukų dirvožemių užterštumo 137Cs ir 90Sr tyrimo duomenys. Aptarti šių elementų susikaupimo, vertikaliojo pasiskirstymo ir migracijos į augalus iki Černobylio AE avarijos ir po jos duomenys, radionuklidu kiekių priklausomybė nuo ilgalaikio tręšimo įvairiomis NPK trąšų normomis, radionuklidų perėjimo į augalus koeficientai. Nustatyta, kad iki Černobylio AE avarijos 137Cs vidutinis aktyvumas vyraujančiuose Lietuvos dirvožemiuose buvo 6,8 ± 1,8 Bq · kg−1, o 90Sr – 5,3 ± 1,2 Bq · kg−1. Durpinių dirvožemių radioaktyvumas – 2–5 kartus didesnis negu šalies mineralinių dirvožemių. Po Černobylio atominės elektrinės avarijos 90Sr kiekis dirvožemyje 1986 m. 0–20 cm sluoksnyje pakito nežymiai. Kai kurių rajonų dirvožemiuose 137Cs vidutiniškai nustatyta 6,7–28,5 Bq · kg−1. Didesnės radionuklidų koncentracijos dirvožemyje aptiktos pietrytiniuose, pietiniuose ir vakariniuose Lietuvos rajonuose. Viršutiniame (0–5 cm) dirvožemio sluoksnyje Vakarų zonoje 137Cs buvo 1,1–1,2 karto daugiau negu 5–20 cm sluoksnyje ir 1,3–2,5 karto daugiau negu 20–40 cm sluoksnyje. Vidurio ir Rytų Lietuvos zonose skirtumai atitinkamai 1,1–1,2 ir 1,2–1,6 karto mažesni. 90Sr ir 137Cs perėjimas iš dirvožemio į augalus vyksta nevienodai ir priklauso nuo dirvožemio savybių bei auginamų augalų. 90Sr perėjimo iš dirvožemio į augalus koeficientai buvo 0,37–0,87, o 137Cs – 0,22–0,53. Ilgametis tręšimas mineralinėmis trąšomis daugeliu atvejų didesnės įtakos 90Sr ir 137Cs kaupimuisi dirvožemyje neturėjo. Reikšminiai žodžiai: dirvožemis, radionuklidai, 137Cs, 90Sr, migracija, Černobylio AE. First Published Online: 14 Oct 2010